2020
DOI: 10.1186/s13018-020-1565-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to long-term results of modified non-vascularized allogeneic fibula grafting combined with core decompression and bone grafting for early femoral head necrosis

Abstract: Purpose The aim of this study was to determine mid-and-long term follow-up results of patients with early femoral head osteonecrosis who were treated by modified free vascularized fibular grafting combined with core decompression and bone grafting. Methods Forty-four patients at early ONFH were included in this study. Visual analog scale (VAS) pain scores, range of hip motion (ROM), and Harris hip score (HHS) were recorded to assess the clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“… 190 Numerous studies have shown that a non‐vascularized fibular allograft combined with CD and bone grafting is a cost‐effective way of improving the survival rate for an early stage of ONFH, delaying disease progression, and improving the quality of patients' lives. 191 , 192 …”
Section: Glucocorticoid‐induced Osteonecrosis Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“… 190 Numerous studies have shown that a non‐vascularized fibular allograft combined with CD and bone grafting is a cost‐effective way of improving the survival rate for an early stage of ONFH, delaying disease progression, and improving the quality of patients' lives. 191 , 192 …”
Section: Glucocorticoid‐induced Osteonecrosis Animal Modelsmentioning
confidence: 99%
“…Eighty hips belonging to 50 SLE patients who underwent free vascularized fibular grafting for ONFH were followed for more than 2 years (average 4.3 years) and the hip score improved in all patients 190 . Numerous studies have shown that a non‐vascularized fibular allograft combined with CD and bone grafting is a cost‐effective way of improving the survival rate for an early stage of ONFH, delaying disease progression, and improving the quality of patients' lives 191–192 …”
Section: Glucocorticoid‐induced Osteonecrosis Animal Modelsmentioning
confidence: 99%
“…Avascular fibular grafting(AVFG) for osteonecrosis of the femoral head was used widely in the past two decades [5].The advances of this operation included smaller trauma(without vascular anastomosis and usually use the allograft),simple technology, less complications and lower expense [6].Researchers had reported the outcomes of a vascularized fibular grafting but the outcomes were various [7][8][9][10].Plenty of literature researches reported that with choosing strictly indications the AVFG might have ideal clinic outcomes as well as FVFG [11].Cheng-Ta Wu et al conducted research regarding a analysis of the necrosis of femoral head with ARCO stage Ⅱ to stage ⅢB that had underwent Non-vascularized bone grafting operation for the treatment. At the final follow-up, 29 hips in 24 patients showed 88.5% of five year survival rate and 76.9% of 12-year survival rate using conversion to THA as the end point [12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] reported that autologous and allogeneic fibular grafts can attain equally good clinical outcomes and high survival rates in long-term follow-up. Plenty of literature researches reported that with choosing strictly indications the AVFG might have ideal clinic outcomes as well as FVFG [ 13 ]. Chen et al .…”
mentioning
confidence: 99%
“…Chen et al . [ 13 ] conducted research regarding a analysis of the necrosis of femoral head with Ficat II that had underwent Non-vascularized bone grafting operation for the treatment. At the final follow-up, 44 patients showed 81.8% of 7-year survival rate using conversion to THA as the end point.…”
mentioning
confidence: 99%